2017
DOI: 10.23846/ow41225
|View full text |Cite
|
Sign up to set email alerts
|

Better Obstetrics in Rural Nigeria study: evaluating the Nigerian Midwives Service Scheme

Abstract: The International Initiative for Impact Evaluation (3ie) is an international grant-making NGO promoting evidence-informed development policies and programmes. We are the global leader in funding, producing and synthesising high-quality evidence of what works, how, why and at what cost. We believe that better and policy-relevant evidence will make development more effective and improve people's lives. 3ie impact evaluations3ie-supported impact evaluations assess the difference a development intervention has mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…This model relies on the assumption that respondents did not select into either of these periods. [2, 3] It also allows us to “sort” eligible respondents by their delivery year, which makes trends in use of obstetric services more obvious. Our first step was to use the ITS model to assess trends in use of obstetric services among rural respondents.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This model relies on the assumption that respondents did not select into either of these periods. [2, 3] It also allows us to “sort” eligible respondents by their delivery year, which makes trends in use of obstetric services more obvious. Our first step was to use the ITS model to assess trends in use of obstetric services among rural respondents.…”
Section: Methodsmentioning
confidence: 99%
“…private sector clinics or non-use/home). [2, 3] Next, we used the ITS model to assess trends in use of obstetric services among urban respondents. Under the null hypothesis, there should be no changes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experience with the existing Federal Government Midwives Service Scheme (MSS) showed that providing midwives in rural clinics was not enough to encourage women to utilize services at PHC facilities [10,11].…”
Section: Introductionmentioning
confidence: 99%